Diferencias sexuales en la violencia desde la perspectiva de la psicología evolutiva: análisis de datos bioarqueológicos de sociedades andinas precoloniales - Pinto dos Santos, Felipe; Vicensotto Bernardo, Danilo (Pontificia Universidad Católica del Perú, 2021)
Motivated by an evolutionary look to understand the origins and circumstances of the practice of physical violence, this study analyzes quantitative data on head injuries in adult individuals, male and female, from pre-colonial Andean populations and discusses its results from the perspective of Evolutionary Psychology, particularly, to explain violent behaviour among males. The results point to a higher prevalence of males in the practice of violence and reveal aspects of the phenomenon that can be studied in the future, such as the differential circumstances of the occurrence of trauma related to gender in past populations.

Motivado por una mirada evolutiva para comprender los orígenes y circunstancias de la práctica de la violencia física, este estudio analiza datos cuantitativos sobre traumatismos craneoencefálicos en individuos adultos, masculinos y femeninos, de poblaciones andinas precoloniales, y discute sus resultados desde la perspectiva de la psicología evolutiva; en particular, para explicar el comportamiento violento entre los individuos masculinos. Los resultados apuntan a una mayor prevalencia de varones en la práctica de la violencia y revelan aspectos del fenómeno que pueden ser estudiados en el futuro, como las circunstancias diferenciales de ocurrencia de traumatismos relacionados con el sexo en poblaciones anteriores.
Sexual differences in violence from the perspective of evolutionary psychology: analysis of bioarchaeological data from Pre-Colonial Andean societies
Keywords: aggression; behaviour; human evolution; trauma; physical violence; agresión; Comportamiento; Evolución humana; Trauma; violencia física; https://purl.org/pe-repo/ocde/ford#6.01.02